Perilaku Ekonomi Pedagang Pasar 46 Kota Jambi - Dindri Nurhaliza Fadila Sari; M. Nazori Madjid; G.W.I Awal Habibah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to find out how the behavior of traders in Pasar 46 Jambi City in the perspective of Islamic marketing ethics and to find out the supporting and inhibiting factors in applying it to traders in Pasar 46 Jambi City. This research is a qualitative research with a descriptive approach. Based on the results of the study it is known that Islamic marketing ethics have not been fully implemented by traders in Pasar 46 Jambi City. Of the 5 indicators of Islamic business ethics 2 that are applied in trading activities at Pasar 46 Jambi City, the responsibility is Ihsan (benevolence). Supporting factors in applying Islamic business ethics to traders in Pasar 46 Jambi City are the factors of responsibility (responsibility) and factors of Ihsan (benevolence). While the factors that become obstacles in applying Islamic business ethics are the monotheism factor (unity), the balance/justice factor (equilibrium), and free will.